2020
DOI: 10.1186/s12876-020-01222-1
|View full text |Cite
|
Sign up to set email alerts
|

Statin and the risk of hepatocellular carcinoma in patients with hepatitis B virus or hepatitis C virus infection: a meta-analysis

Abstract: Background: Statin may confer anticancer effect. However, the association between statin and risk of hepatocellular carcinoma (HCC) in patients with hepatitis B virus (HBV) or hepatitis C (HCV) virus infection remains inconsistent according to results of previous studies. A meta-analysis was performed to summarize current evidence. Methods: Related follow-up studies were obtained by systematic search of PubMed, Cochrane's Library, and Embase databases. A random-effect model was used to for the meta-analysis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
2
18
0
1
Order By: Relevance
“…Initial search identified 15 studies. Search in the references of published systematic reviews [ 9 11 , 29 , 30 ] , did not identify additional articles. Search in the reference list of one review article [ 8 ] identified four additional articles.…”
Section: Resultsmentioning
confidence: 99%
“…Initial search identified 15 studies. Search in the references of published systematic reviews [ 9 11 , 29 , 30 ] , did not identify additional articles. Search in the reference list of one review article [ 8 ] identified four additional articles.…”
Section: Resultsmentioning
confidence: 99%
“…In the Swedish nationwide cohort including chronic hepatitis B and C patients, the use of lipophilic statins decreased the cumulative incidence of HCC (aHR: 0.41; 95%CI: 0.32-0.61) [78] . A recent meta-analysis, including 7 studies with HBV carriers revealed that statin therapy reduced the risk of HBVrelated HCC with a relative risk of 0.52 (95%CI: 0.40-0.68; P < 0.001) [79] .…”
Section: Non-anti-hbv Therapymentioning
confidence: 99%
“…The definition of statin users (≥28‐30 cumulative defined daily dose) involves widely accepted criteria. ( 4 ) The limitations of the study prevented us from drawing definitive conclusions, but the study findings support the potential benefit to patients with chronic hepatitis B and warrant a further prospective and randomized controlled trial.…”
mentioning
confidence: 80%